2010
DOI: 10.1128/aac.00915-09
|View full text |Cite
|
Sign up to set email alerts
|

Penicillin-Binding Protein Gene Alterations in Streptococcus uberis Isolates Presenting Decreased Susceptibility to Penicillin

Abstract: Streptococcus uberis is an environmental pathogen commonly causing bovine mastitis, an infection that is generally treated with penicillin G. No field case of true penicillin-resistant S. uberis (MIC > 16 mg/liter) has been described yet, but isolates presenting decreased susceptibility (MIC of 0.25 to 0.5 mg/liter) to this drug are regularly reported to our laboratory. In this study, we demonstrated that S. uberis can readily develop penicillin resistance in laboratory-evolved mutants. The molecular mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 24 publications
3
19
0
1
Order By: Relevance
“…2). The equilibrium inhibitor dissociation constant (K i ) is in the micromolar range and comparable to that reported previously (8,12,18). These data suggest that both PBP1a/1b and PBP2a/2b/2x mutations are contributing to reduced susceptibility.…”
supporting
confidence: 88%
“…2). The equilibrium inhibitor dissociation constant (K i ) is in the micromolar range and comparable to that reported previously (8,12,18). These data suggest that both PBP1a/1b and PBP2a/2b/2x mutations are contributing to reduced susceptibility.…”
supporting
confidence: 88%
“…In France, the CA-SFM recommends that penicillin resistance is suspected for all non-pneumococcal streptococci isolated from animals when a decreased susceptibility to 5 mg oxacillin is detected by disc diffusion (resistant if ,21 mm). Since it was recently shown that S. uberis can develop resistance to penicillin in vitro (Haenni et al, 2010), and since isolates presenting decreased susceptibility have already been reported (Guerin-Faublee et al, 2002;Mevius et al, 2007;Rossitto et al, 2002), this work intended to further characterize field isolates classified as either oxacillin resistant or oxacillin sensitive, in order to get a better insight of the potential population shift towards penicillin resistance in S. uberis.…”
mentioning
confidence: 99%
“…10 Invitro experiments demonstrated that S. uberis can readily develop penicillin resistance, and microbial analysis of bacterial population in treated milk showed that S. uberis can grow even in cold storage. 11,12 It has been hypothesized that the stability of this pathogen under various environmental conditions and the expression of virulence factors 11-13 may expand the pathogenicity of this bacterium from cattle to humans as described for Streptococcus agalactiae, a pathogen that is associated with both animal and human diseases. 14 However, few data provide support for this hypothesis, and in many cases the tests used for the identification of S. uberis in humans have been debated.…”
Section: Discussionmentioning
confidence: 99%